TECHNOLOGIES FOR THE DEVELOPMENT OF METHODOLOGICAL COMPONENT IN FUTURE MUSIC TEACHERS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
The article talks about future music teachers and their professional competence. In order to reveal the topic of the article, research developments in this field were used. Conclusions from the article can be used in training music teachers.